PSVI-7 Effects of Increasing Total Dietary Fiber During Gestation and the Pre-Farrowing Period on Sow and Litter Performance in Lactation. (12th April 2022) - Martinez, Gabriela E; Rosero, David; Wilcock, Pete; Paz, Ximena; van Heugten, Eric
Abstract: This study evaluated the effects of increasing total dietary fiber (TDF) during gestation and the pre-farrowing period to improve sow and litter performance. Sows (n = 117) were assigned to a 2×2 factorial arrangement consisting of the following factors: 1) gestation diet with low fiber (9% TDF) or high fiber (18%TDF) using primarily wheat middlings and soyhulls as the fiber sources; and 2) pre-farrowing pelleted supplement (no top-dress or top-dress). The top-dress was formulated to contain 43% TDF, using soyhulls and wheat middlings as the fiber sources and was provided at 0.91 kg daily on top of the normal feed allotment from the time sows were transferred into the farrowing house (112±1 d of gestation) until parturition. Fiber composition of the gestation diet and additional fiber from the top-dress fed pre-farrowing did not impact sow BW at placement ( P = 0.39) or at weaning ( P = 0.48). High fiber supplementation during gestation reduced the entry-to-farrow days ( P = 0.007). The number of pigs born alive tended ( P = 0.10) to be greater for sows fed the top-dress (13.03 and 12.88, within low and high fiber diets, respectively) compared with sows not receiving top-dress (11.89 and 11.42). Number of stillborn pigs (1.58, 1.26, 1.30, and 1.64 for the high fiber without and with top-dress, and low fiber without and with top-dress, respectively, P = 0.75) and number of weaned pigs (9.96, 10.30, 9.56, and 9.72) were not impacted by dietary treatments ( P = 0.64). However, number of small weaned pigs was less when top-dress was provided to sows fed low fiber diets compared with top-dress supplementation to high fiber diets (0.33 vs 1.30; interaction, P = 0.02). Results suggest that high fiber supplementation during gestation and additional fiber fed immediately pre-farrowing did not influence sow BW, whereas top-dress tended to increase the number of pigs born alive and decreased the number of non-viable pigs at weaning when added to low fiber diets.